Differences between Breakfast Consumption and Snack Consumption of Elementary School Children on Feelings of Sleepiness at SD Negeri 2 Kedungwaru Tulungagung - Radono, Panca; Akbar, Rijal Maulana (Journal of Global Research in Public Health, 2022)
The optimal growth of school-age children depends on providing nutrition with good and right quality and quantity. The purpose of this study was to determine differences in consumption of breakfast and consumption of snacks for elementary school children to drowsiness in SD Negeri 2 Kedungwaru Tulungagung. In this study using observational research design with a cross-sectional approach. The population is all grade 3-5 students at SDN 2 Kedungwaru Tulungagung with a sample of 47 respondents stratified random sampling. Data were obtained from questionnaires and processed by independent T test statistic test. The results showed that the average breakfast group consumed breakfast 5 times a week, while the snack group consumed snacks 18 times a week, or 3 times a day. And the mean value of drowsiness in the breakfast group was 37.79. Whereas in the snack group the mean value of drowsiness is 49.74 from the maximum value. Statistical test results obtained P value 0.012 <α 0.05 then H0 is rejected which means that there is a difference in consumption of breakfast and consumption of snacks for elementary school children to drowsiness in SD Negeri 2 Kedungwaru Tulungagung. Consuming breakfast is more effective to maintain concentration and reduce drowsiness when learning compared to consuming jajanan food.